Dietary Glucosinolate Intake, Polymorphisms in Selected Biotransformation Enzymes, and Risk of Prostate Cancer - Steinbrecher, Astrid; Rohrmann, Sabine; Timofeeva, Maria; Risch, Angela; Jansen, Eugène; Linseisen, Jakob (Cancer epidemiology, biomarkers & prevention, 2010)
A protective role of glucosinolates in prostate cancer development might be mediated by the induction of biotransformation enzymes. These enzymes, enhancing the elimination of carcinogens from the body, are known to be polymorphic. Therefore, we evaluated whether a possible association between glucosinolate intake and prostate cancer risk is modified by polymorphisms in GSTT1, GSTM1, GSTA1, GSTP1 , or NOQ1 genes. A case-control study including 248 prostate cancer cases and 492 matched controls was nested in the prospective European Prospective Investigation into Cancer and Nutrition-Heidelberg cohort. At baseline, participants provided dietary and lifestyle data and blood samples, which were used for genotyping and measurement of serum glutathione S -transferase-α concentration. Odds ratios and 95% confidence intervals were calculated by conditional logistic regression. We found an inverse association of glucosinolate intake with prostate cancer risk (adjusted odds ratio, 0.72 per 10 mg/d increment; 95% confidence interval, 0.53-0.96). Stratification by genotype showed significantly reduced risks for subjects with wild-type of NQO1 (C609T) compared with CT or TT carriers ( P interaction = 0.04). Those with deletions in both GSTM1 and GSTT1 genes combined had a significantly reduced risk with increasing glucosinolate intake ( P interaction = 0.01). There was no effect modification of glucosinolate intake and cancer risk by GSTA1 (G-52A) or GSTP1 (A313G) genotype, but serum glutathione S -transferase-α concentrations were inversely associated with prostate cancer. This study showed that the inverse association between glucosinolate intake and prostate cancer risk was modified by NQO1 (C609T) and GSTM1 and GSTT1 deletion polymorphisms. This information will help to further elucidate the mechanism of action of potentially protective substances in vivo . Cancer Epidemiol Biomarkers Prev; 19(1); 135–43